IMPLEMENTASI PERIZINAN WARUNG INTERNET BERDASARKAN PERATURAN DAERAH KOTA SURAKARTA NOMOR 4 TAHUN 2016 TENTANG PENYELENGGARAAN WARUNG INTERNET TERKAIT PENGENDALIAN PORNOGRAFI - Firmansyah, Abdul Hady; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This study aims to determine the implementation of internet’s cafe licensing based on Surakarta City Regional Regulation Number 4 of 2016 concerning the operation of internet cafes related to control pornography. The research method used is a type of empirical legal research with the nature of descriptive research. The research approach used is a qualitative approach with research locations in the Surakarta City Government. The type and source of research data is divided into primary data and secondary data with data collection techniques consisting of interview techniques and literature study. Data analysis techniques used are qualitative analysis techniques. Based on the results of the research that the author did, it was known that the implementation of internet cafe business licensing related to pornography control was classified into 2 main aspects namely procedural aspects related to the implementation of licensing carried out by the Investment and Integrated Licensing Agency of Surakarta City Government (BPMPT) with various terms and conditions and Substantive aspects relating to the supervision of internet cafe businesses related to pornography control with technical requirements carried out by the Department of Transportation, Communication and Information of Surakarta City (Dishubkominfo).